Rotator cuff tears: repair and reconstruction. Issue 3 (June 2018) - Gibbs, Victoria Naomi; Raval, Parag; Rees, Jonathan L.; Gwilym, Stephen E.
Abstract: The management of rotator cuff pathology amongst surgeons can vary widely. 1 In recent years, there have been increasing efforts to standardize treatment. However, the evidence base for repair and reconstruction for rotator cuff tears is limited. In this article we review some of the current evidence available for the management of these tears and aim to better equip the surgeon in the decision making process. The article focuses on the surgical options for the management of cuff tears and aims to inform on how to repair torn rotator cuff tendons,  including surgical techniques and current concepts on reconstruction, discussion on timing of repair and the pitfalls and challenges which can be faced when attempting to repair large tears.